Critical Analysis of Quality-of-Life Domains from Primary to Adjuvant Treatment Stages in Breast Cancer Patients - Sanjiv Srivastava; Alpana Srivastava; Sandeep Tiwari (Shiraz University of Medical Sciences, 2022)
Objective  To study the changes in quality of life (QoL) domains in breast cancer patients during the treatment and follow-up.   Methods A cross-sectional study was conducted at King George's Medical University, Lucknow, UP. Data were collected using a two-part questionnaire. In the first part, demography, disease and treatment details and related information were collected. In the second part, a validated scale developed by Ferrel for evaluating QoL of breast cancer patients was used. Over 150 patients diagnosed with breast cancer at King George Medical University, Lucknow, India (KGMU) were sampled. Baseline along with two follow-ups were done for the same patient to see the changes in QoL's domains during treatment. Analysis of variance technique (ANOVA) was used to see the association between QoL domains and effect of treatment.   Results A total of 150 patients were interviewed and their average QoL index was built by using index number approach. Average QoL was found to be 0.3433 during baseline which mildly improved in the first follow-up to 0.3744 and more in the second follow-up to 0.419. The major reason is that 74% belonged to low economic status and occurrence of cancer further deteriorated the situation for them. During the adjuvant treatment, though it deteriorated their physical condition, hope of getting better improved psychological conditions and after nine months of treatment their both conditions improved. Major factors which affected quality of life of patients during the treatment were fatigue, pain, and fear of recurrence and spread of cancer.   Conclusion Geographical area, socioeconomic status, education, and type of treatment, especially non-adjuvant and adjuvant therapy, significantly affect QoL among breast cancer patients. To develop a customized intervention, psychological counselling centres are the need of the hour.